Higher levels of circulating naïve CD8+CD45RA+ cells are associated with lower extent of coronary atherosclerosis and vascular dysfunction. (15th May 2018) - Podolec, Jakub; Niewiara, Lukasz; Skiba, Dominik; Siedlinski, Mateusz; Baran, Jakub; Komar, Monika; Guzik, Bartlomiej; Kablak-Ziembicka, Anna; Kopec, Grzegorz; Guzik, Tomasz; Bartus, Krzysztof; Plazak, Wojciech; et al.
Highlights: Lower levels of young cytotoxic T-cell progenitors were observed in advanced CAD. PWV correlates negatively with CD8 + CCR7 + CD45RA + cell levels in patients without CAD. Levels of cytotoxic cell progenitors may become a biomarker of early CAD.